2018
DOI: 10.1016/j.bbrc.2018.06.126
|View full text |Cite
|
Sign up to set email alerts
|

The HMW2 adhesin of non-typeable Haemophilus influenzae is a human-adapted lectin that mediates high-affinity binding to 2–6 linked N-acetylneuraminic acid glycans

Abstract: Non-typeable Haemophilus influenzae (NTHi) is a human-adapted bacterial pathogen, responsible for infections of the human respiratory tract. This pathogen expresses a range of adhesins that mediate binding to host cells. Most NTHi strains can express the related adhesins HMW1 and HMW2. Expression of HMW proteins is phase-variable: changes in the length of simple-sequence repeats located in the encoding genes promoter regions results in changes in expression levels of these adhesins. HMW expression is also cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…A number of human-adapted bacterial pathogens also specifically target Neu5Ac in preference to Neu5Gc; for example, Streptococcus pneumoniae preferentially recognizes and utilizes Neu5Ac (71), and the toxin produced by Salmonella enterica serovar Typhi has a much higher affinity for cells with Neu5Ac-containing glycan structures than for those containing Neu5Gc (72). We recently reported that two major adhesins of NTHi, the HMW1/2 proteins, preferentially bind Neu5Ac sialic acid-containing glycans over Neu5Gc-containing glycans (73), demonstrating that NTHi preferentially binds glycans present in the human host. Our findings reported in this study indicate the molecular basis for a further host adaptation in NTHi.…”
Section: Discussionmentioning
confidence: 99%
“…A number of human-adapted bacterial pathogens also specifically target Neu5Ac in preference to Neu5Gc; for example, Streptococcus pneumoniae preferentially recognizes and utilizes Neu5Ac (71), and the toxin produced by Salmonella enterica serovar Typhi has a much higher affinity for cells with Neu5Ac-containing glycan structures than for those containing Neu5Gc (72). We recently reported that two major adhesins of NTHi, the HMW1/2 proteins, preferentially bind Neu5Ac sialic acid-containing glycans over Neu5Gc-containing glycans (73), demonstrating that NTHi preferentially binds glycans present in the human host. Our findings reported in this study indicate the molecular basis for a further host adaptation in NTHi.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of TCTTTCA (n) repeats in this SSR increases, the level of expression of HMW1/2 decreases [26]. HMW1/2 are required for binding to related host cell receptors in the human airway [27,28], but they are also highly immunogenic, and are currently being investigated as a candidate for a vaccine against NTHi [29,30].…”
Section: Phase-variable Expression Of Genes Via Genetic Mechanismsmentioning
confidence: 99%
“…The HMW1 protein binds to host cell glycans as cellular receptors, specifically α2-3-sialyllactosamine (2-3 SLN) ( 19 ). We recently demonstrated that HMW2, which is ∼65% identical to HMW1, binds the related glycan α2-6-sialyllactosamine (2-6 SLN), with high specificity for 2-6 SLN containing N -acetylneuraminic acid (Neu5Ac), the form of sialic acid expressed by humans ( 20 ). Intriguingly, 2-3 SLN is found mainly in the lower human respiratory tract, whereas 2-6 SLN is found throughout the entire respiratory tract but predominates in the upper airway ( 21 ).…”
Section: Introductionmentioning
confidence: 99%